2008
DOI: 10.1021/ie8005484
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Transfer Performance of a Liquid−Liquid Microdispersed System

Abstract: In this work, the heat-transfer performance of liquid-liquid microdispersed systems was tested for the first time with a microdispersion contactor named a membrane dispersion minicontactor and octane/water as the working system. The volumetric heat-transfer coefficients ranging from 5 to 25 MW/(m 3 • °C) were obtained, which were 15-20 times higher than that of the conventional dispersion heat-transfer methods. The heattransfer Murphree efficiencies, defined to evaluate the heat-transfer performance, reached 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…During recent years, microdispersed liquid/liquid and gas/liquid systems have caught the attention of many researchers for their controllable flow and effective transport properties. It has been found that the heat and mass transfer rates can be significantly increased with the reduction of dispersed size 1–3. By using microfluidic devices, micromonodispersed bubbles and droplets can be prepared, which are more useful for research and production processes.…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, microdispersed liquid/liquid and gas/liquid systems have caught the attention of many researchers for their controllable flow and effective transport properties. It has been found that the heat and mass transfer rates can be significantly increased with the reduction of dispersed size 1–3. By using microfluidic devices, micromonodispersed bubbles and droplets can be prepared, which are more useful for research and production processes.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the coalescence of microdroplets in the observed process, the size of microdroplets in the liquid−liquid microdispersion system ranged from 30 to 50 μm while changing the continuous flow rate. According to the research of Wang et al 36 in the liquid−liquid microdispersion system, the mass transfer coefficient of the liquid−liquid microdispersion system could be calculated with a value of 0.73 m/s, so it is feasible to provide a low concentration distribution for the Ti species and lead to a co-condensation with oligomeric silicate solution in this novel system for high-quality TS-1 particles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A phenomenological model for heat transfer was validated with experimental data (Lemenand et al, 2010) and longitudinal embedded vorticity was identified as the main intensification factor for heat transfer. Finally, using a microdispersion contactor, Wang et al (2008) studied heat transfer microdispersing hot octane and hexane into cold water, by cross flow of the oil phase into water through a membrane. Significant enhancement in heat transfer was observed due to dispersion with up to a 15-20 increase in the volumetric heat transfer coefficients compared to a conventional dispersed system.…”
Section: Heat Transfer To Liquid-liquid Mixturesmentioning
confidence: 99%